Analysis of pregnancy and neonatal outcomes in 100 pregnant women with Rh-negative blood type - Bing-Cai Bi; Hong-Yan Yang; Jun-You Su; Li Deng (BMC Pregnancy and Childbirth)
Abstract Background This study aimed to explore variations in prenatal care, delivery methods, influencing factors, and neonatal outcomes among Rh-negative pregnant women, so as to improve pregnancy healthcare for this demographic, raise the quality of maternal–fetal management, and safeguard the health of both mother and infant. Methods This study included 200 women who received routine prenatal care, exhibited no other pregnancy complications, and were admitted for delivery. They were divided into an observation group (100 Rh-negative blood type) and a control group (100 Rh-positive blood type). The study examined differences in pregnancy management, clinical characteristics and pregnancy outcomes between the two groups. Results The results indicated that singleton pregnancies in Rh-negative mothers are associated with significantly higher rates of postpartum blood loss (305.1 ± 183.8 vs. 246.1 ± 84.9 mL, P = 0.004), neonatal hyperbilirubinemia (39% vs. 23%, P = 0.014), low birth weight (11% vs. 2%, P = 0.01), and NICU admission (30% vs. 18%, P = 0.046) compared to the control group. Among Rh-negative mothers, subgroup analysis by ethnicity revealed a higher incidence of fetal distress in the other ethnic groups compared to the Han and Zhuang groups (16.7%, 0, 6.5%, respectively, P = 0.025). Subgroup analysis based on ABO blood type within Rh-negative mothers did not show any statistical significance in various outcomes (all P > 0.05). Infants with neonatal hyperbilirubinemia born to Rh-negative mothers experienced a quicker resolution of hyperbilirubinemia compared to those whose mothers did not receive intramuscular anti-D immunoglobulin [1.0 (1.0, 1.5) vs. 5.0 (1.5, 10.0), P = 0.002]. Conclusions The Rh-negative blood type is linked to higher risks of neonatal hyperbilirubinemia, low birth weight, and increased postpartum hemorrhage, resulting in detrimental pregnancy outcomes. Administering anti-D immunoglobulin speeds up the resolution of neonatal hyperbilirubinemia. Thus, prudent and efficient use of anti-D immunoglobulin can mitigate adverse outcomes for both mothers and newborns.